In Vitro Antioxidant and Thrombolytic Activities of Bridelia Species Growing in Bangladesh (Journal of Scientific Research, 2013)
The organic soluble extractives of three Bridelia species, B. verrucosa, B. stipularis and B. tomentosa growing in Bangladesh were subjected to screening for free radical scavenging activity, total antioxidant capacity and total phenolic content. All of the methanol extracts of the these plants and their kupchan fractions showed moderate to strong free radical scavenging activity, the total antioxidant capacity and total phenolic content, of which the methanol extract of the leaf of B. verrucosa revealed highest activity having IC50 value of 6.35 ?g/ml. All the extractives of three plants were also studied for their thrombolytic potential. Among the three plants the carbon tetrachloride soluble fraction and methanol extract of leaf and aqueous soluble fraction of bark of B. tomentosa, methanol extract of bark of B. stipularis and carbon tetrachloride soluble fraction of leaf of B. verrucosa exhibited highest thrombolytic activity with clot lysis value of 41.46%, 34.85%, 37.04%, 36.45% and 33.72%, respectively. Standard streptokinase was used as positive control which exhibited 61.50% lysis of clot while the negative control water revealed 2.56% lysis of clot.Keywords: Antioxidant; Free radical scavenging; Total antioxidant capacity; Phenolic content; Thrombolytic activity; Bridelia.© 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i2.13568        J. Sci. Res. 5 (2), 343-351 (2013)